2018
DOI: 10.1002/bem.22135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of large gradient high magnetic field (LG‐HMF) on the long‐term culture of aquatic organisms: Planarians example

Abstract: Large gradient high magnetic field (LG-HMF) is a powerful tool to study the effects of altered gravity on organisms. In our study, a platform for the long-term culture of aquatic organisms was designed based on a special superconducting magnet with an LG-HMF, which can provide three apparent gravity levels (µ g, 1 g, and 2 g), along with a control condition on the ground. Planarians, Dugesia japonica, were head-amputated and cultured for 5 days in a platform for head reconstruction. After planarian head regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Their results demonstrate that all of the planarians normally regenerated their heads and the regeneration rate of the four groups is similar. These results indicate that planarians can correctly regenerate their heads at different gravity environments [25].…”
Section: Physiological Effects Of Altered Gravity and Magnetic Fieldmentioning
confidence: 65%
See 2 more Smart Citations
“…Their results demonstrate that all of the planarians normally regenerated their heads and the regeneration rate of the four groups is similar. These results indicate that planarians can correctly regenerate their heads at different gravity environments [25].…”
Section: Physiological Effects Of Altered Gravity and Magnetic Fieldmentioning
confidence: 65%
“…These results showed that LG-HMF-generated microgravity and hypergravity did not affect the reestablishment of photonegative ability. But the photonegative response time of the planarians which regenerated under LG-HMF conditions was slightly suppressed, and the authors thought it was mainly due to the difference of the locomotor system instead of the reconstructed head [25]. They took the traditional planarian locomotor velocity (pLMV) assay and automated center-of-mass (COM) tracking approach and image analysis to analyze the locomotor behaviors, and the results showed that Group ug/12T has a significantly decreased locomotor function compared to the other three groups during the 8 min test.…”
Section: Physiological Effects Of Altered Gravity and Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these unique adult stem cells and their plasticity renders planarians in a unique model to study the impact of environmental factors like hypergravity and vibration in adult cells in the context of a "whole animal", in contrast to the partial view inherent to "in vitro" cell cultures. Also, there is an increasing interest to study these animals under various altered gravity conditions [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…npj Microgravity (2020)25 Published in cooperation with the Biodesign Institute at Arizona State University, with the support of NASA1234567890():,;…”
mentioning
confidence: 99%